Impact of Macroeconomic News Surprises on Interest Rate Swap Spreads - Fang, V. (Institutional Knowledge at Singapore Management University, 2010)
This study examines the response of Australian interest rate swap spreads to the arrival of macroeconomic news during economic expansion and contraction. We find the degree that news surprises impact on swap spread depends largely on the state of the economy. Unexpected inflation rate is the only news release that has significant impact on swap spreads across all maturities during contractions and remains the important news announcement throughout the business cycle, while unanticipated unemployment rate tends to be more relevant for the 10-year swap and the unanticipated change in money supply tends to be more relevant for 4-and 7-year swaps during expansions. We also find that shocks from these news surprises significantly impact the conditional volatility of the swap spread change during both economic expansion and contraction. The macroeconomic shocks in general are negatively related to the conditional volatility of the swap spread change, suggesting that news worthy announcements tend to reduce uncertainty on the news announcement days in the swap market during both economic expansion and contraction.